Factors Influencing Students ’ Academic Achievements in Science - Laizāne, Ināra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Issue of educational quality is becoming more and more actual in the whole world. One of the tasks of European Union in the field of education is to provide the quality of education. In this article the educational quality in science has been looked at. The aim and method of the research are revealed in the article. The research has been done with the aim to find out the students’ academic achievements in science and the tendencies of factors that influence them. With the help of quantitative method (questionnaire) the assessment method of academic achievements was explained. In order to measure students’ achievements, the results obtained by summative assessment were used. The tendencies of factors influencing academic achievements in science were explored by looking for correlative relevance that promote and delay students’ academic achievements in science. The data obtained in the research was analysed quantitatively and qualitatively.